Psihološki dejavniki in posledice, ki vzdržujejo simptomatiko nihajne poškodbe vratu - Horvat Rauter, Barbara (Rehabilitacija (Ljubljana), 2020)
Introduction: Whiplash-associated disorders account for a large proportion of the overall impairment and disability. Five years after the injury only half of patients with whiplash injury fully recover. It is estimated that 5 % develop long-term disability with impairments in cognition, emotional functioning and physical activity. In addition to a literature review, we present a case of a man with long-term disability after whiplash injury. Methods: This is a case study of a man who suffered whiplash injury in 2014, when he was 30 years old. The symptoms remained present five years after the injury, which is why he was sent to psychological assessment in 2019. We used the Detailed Assessment of Posttraumatic Stress (DAPS), the Personality Assessment Inventory (PAI) and the Rorschach test to assess him. Results: Results of the psychological assessment show clinically significant deviations especially in the domain of posttraumatic symptoms. His stress-coping competences are low and his personality is vulnerable. There are difficulties with mood disorders. Conclusions: Pre- and post-injury psychological factors maintain the whiplash injury symptoms. In the presented case, the man's personality structure, anxiety, low stress-coping strategies and depression are the main risk factors.
Keywords: case study; dejavniki tveganja; learning risk factors; nihajna poškodba vratu; prikaz primera; psihološke posledice; psychological consequences; psychology; Whiplash Injuries; whiplash injury